Good Corporate Governance Memoderasi Hubungan Profitabilitas, Likuiditas, Leverage dan Firm Size Terhadap Tax Avoidance - Gusti Ayu Oppie Indra Widnyani; I Putu Gede Diatmika; Gede Adi Yuniarta (SAINTIS Publishing, 2025)
The government continues to make efforts to increase state revenue from the tax sector. However, for companies, taxes are often viewed as a burden that can reduce profits. As a result, companies with large profits tend to find ways to minimize their tax burden, one of which is through tax avoidance practices. This study aims to examine the influence of profitability, liquidity, leverage, and firm size on tax avoidance, as well as the role of Good Corporate Governance (GCG) as a moderating variable. The research objects are companies listed in the LQ45 Index on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The sample was selected using purposive sampling; out of 45 companies, 27 met the criteria, resulting in 135 observations over the five-year period. Data were analyzed using the Partial Least Squares (PLS) method through outer model testing, inner model, and path coefficient analysis using the SmartPLS software. The results show that profitability, liquidity, and firm size have a significant negative effect on tax avoidance. Meanwhile, leverage does not show a significant effect. GCG has a positive effect on tax avoidance and is able to weaken the influence of liquidity and firm size on tax avoidance. However, GCG does not succeed in moderating the effect of profitability and leverage on tax avoidance.